A survey of some plasma metabolites and haematological parameters of grazing White Fulani cattle and Kano Brown goats in Nigeria - Okorie, A.U.; Anugwa, F.O.I. (1986)
Blood samples were taken from 36 White Fulani cattle and 36 Kano Brown goats over a period of 12 weeks in the dry season and analyzed for haemoglobin (Hb), red blood cell (RBC) count, white blood cell (WBC) count, packed cell volume (PCV), plasma ammonia-N (PAN) and plasma Urea-N (PUN). Rumen ammonia concentration (RAC) was determined in the cattle only. In the White Fulani, the values for Hb, RBC, WBC, and PCV were 11.53g/100 ml; 6.5 million/cu mm; 7.18 thousand/cu mm and 32.03 per cent, respectively. Plasma ammonia and plasma urea were 0.22 mg/100 ml and 1.11 mg/100 ml respectively. In the Kano Brown goats, the mean values for Hb, a RBC, PCV, plasma ammonia and plasma urea were 12.04 per cent, 12.08 million / cu mm, 7.76 thousand/cu mm, 32.9 per cent, 0.24 mg/100 ml and 1.08 mg/l00ml, respectively. In White Fulani cattle PCV was linearly related to Hb (r=0.45, P